Patterns of genetic diversity in five species of Passeriformes co-distributed in an environmental gradient - Marcela Restrepo-Arias; Héctor F. Rivera-Gutiérrez; Iván Darío Soto-Calderón; Ernesto Pérez-Collazos; Catalina González-Quevedo (Avian Research, 2025)
Understanding the evolutionary processes that influence the distribution of genetic diversity in natural populations is a key issue in evolutionary biology. Both species' distribution ranges and environmental gradients can influence this diversity through mechanisms such as gene flow, selection, and genetic drift. To explore how these forces interact, we assessed neutral and adaptive genetic variation in three widely distributed and two narrowly distributed bird species co-occurring along the Cauca River canyon in Antioquia, Colombia—a region of pronounced environmental heterogeneity. We sampled individuals across eight sites spanning the canyon's gradient and analyzed genetic diversity and structure using microsatellites and toll-like receptors (TLRs), a gene family involved in innate immunity. Widely distributed species consistently exhibited higher genetic diversity at both marker types compared to their narrowly distributed counterparts. Although we did not find a significant relationship between microsatellite heterozygosity and TLR heterozygosity, we evidenced a negative trend for widely distributed species and a positive trend for narrowly distributed species. This result suggests that there is a stronger effect of genetic drift in narrowly distributed species. Our results highlight the role of distribution range in maintaining genetic diversity and suggest that environmental gradients, by interacting with gene flow and selection, may influence patterns of adaptive variation.